Experimental Study on Ultrasonic Cavitation Intensity Based on Fluorescence Analysis - Linzheng Ye; Shida Chuai; Xijing Zhu; Dong Wang (Chinese Journal of Mechanical Engineering, 2023)
Abstract The Ultrasonic cavitation effect has been widely used in mechanical engineering, chemical engineering, biomedicine, and many other fields. The quantitative characterization of ultrasonic cavitation intensity has always been a difficulty. Based on this, a fluorescence analysis method has been adopted to explore ultrasonic cavitation intensity in this paper. In the experiment of fluorescence intensity measurement, terephthalic acid (TA) was used as the fluorescent probe, ultrasonic power, ultrasonic frequency, and irradiation time were independent variables, and fluorescence intensity and fluorescence peak area were used as experimental results. The collapse of cavitation bubble will cause molecular bond breakage and release ·OH, and the non-fluorescent substance TA will form the strong fluorescent substance TAOH with ·OH. The spectra of the treated samples were measured by a F-7000 fluorescence spectrophotometer. The results showed that the fluorescence intensity and fluorescence peak area increased rapidly after ultrasonic cavitation treatment, and then increased slowly with the increase of ultrasonic power, which gradually increased with the increase of irradiation time. They first decreased and then increased with the increase of ultrasonic frequency from 20 kHz to 40 kHz. The irradiation time was the most influential factor, and the cavitation intensity of low frequency was higher overall. The fluorescence intensity and fluorescence peak area of the samples increased by 2–20 times after ultrasonic treatment, which could increase from 69 and 5238 to 1387 and 95451, respectively. After the irradiation time exceeded 25 min, the growth rate of fluorescence intensity slowed down, which was caused by the decrease of gas content and TA concentration in the solution. The study quantitatively characterized the cavitation intensity, reflecting the advantages of fluorescence analysis, and provided a basis for the further study of ultrasonic cavitation.